Case Report: Excellent long survival of a female patient with Osteosarcoma still alive after 21 years’ management in Babil Oncology Center (1998-2019) - Al-Alawachi, Sharif Fadhil; Al-Tahan, Abud Al Wahab; Abdulzahra, Hussein; Fadhil FAdhil, Mohammed Saeed Shareef; Hassan, Ph. Lamyaa Jaber; Fadhil, Ali Shareef Fadhil (International Journal of Psychosocial Rehabilitation, 2020)
30 years old unmarried girl with above knee amputation of right lower limbs since 1998 as radical treatment for Osteosarcoma of upper tibia with no systemic or local recurrence after oncological treatment till now.